IDENTIFIKASI TINGGALAN ARKEOLOGIS DI SITUS BENTENG LIYA KECAMATAN WANGI-WANGI SELATAN, KABUPATEN WAKATOBI - La Ode Nur Akbar; sitti kasmiati (SANGIA: Jurnal Penelitian Arkeologi, 2019)
The formulation of the problem in this study is (1) What are the archaeological remains found on the siteof Fort Liya. (2) How is the distribution of remains at the Fort Liya Site in the kingdom of Buton. (3) What is theFunction of the Liya Fortress during the Buton Kingdom. The objectives in this study are (1) To find out anddescribe the archaeological remains found in the Fort Liya Site. (2) To be able to find out how the distributionpattern of the Fort Liya Site during the Buton Kingdom. (3) To be able to know and explain the functions of FortLiya during the era of Buton.The results of this study indicate that the archaeological remains in the Liya Fortress Site in the formofTondo / Benteng Wall, Lawa / Pintu which number 14 (fourteen) as the names are; Balalaoni, Eflaa, Bisitio, Timi,Ntooge, Puru, Godho, Baringi, Lingu, Wotea, Tambaa, Bente, Ewatu, Bantu and Woru, Baluara / Bastion, MasjidMubaraq, Bharuga, Liyang / Lubang Batu, Bhadili / Meriam Kuna, Kamali / Raja's house, Makam Raja, WatuSahuu, and Lesung Batu. Distribution Pattern of Liya Layer 1 Fortress, is the main layer which is a residentialarea is the main defense center and the central government of Liya kingdom as well as the center of itssupporting activities, Layer II, is a defense layer of the area surrounded by coral structure and each main side isgate or entrance and, Layer III, is a layer of defense of natural areas which according to the local community are characterized by stone monuments and placed in the 4 corners of the wind eye position of the fort and itsfunction as a reconnaissance place as well as natural defense